Conditions of faith - Miller, Alex, 1936- (St Leonards, N.S.W. : Allen & Unwin, 2000)
In the 1920s, Emily Stanton leaves Melbourne to live in Paris with her new husband. Her marriage awakens in her an ardent desire to find a reason for living, a desire which leads her to flirt with risk, passion and unorthodox friendships, and carries her to Tunisia. From the winner of the Commonwealth Writers Prize.
Keywords: Identity -- Fiction; Identity -- Fiction; Love stories; Australian fiction; Love stories; Australian fiction